A fiber-reinforced resin-based lightweight ablative composite material with a gradient structure and a preparation method thereof
By pre-occupying the phase change material on the fiber felt and filling it with ceramicable resin, the gradient structure of phenolic aerogel and ceramicable resin bimatrix is solved by ablation of fiber reinforced resin-based light ablation composite at high temperature. The pyrolysis and structural collapse problems in the environment have achieved excellent mechanical strength, thermal insulation and ablation resistance, and maintained the integrity and stability of the composite material.
Patent Information
- Application Number
- CN202410893734.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-04
AI Technical Summary
Existing fiber-reinforced resin-based light-ablative composites are prone to pyrolysis and vaporization under high-temperature ablation environment, resulting in material weight loss and structure collapse. The existing gradient design methods are difficult to maintain the composite during long-term ablation. integrity and stability.
By pre-occupying phase change material on the outer surface of the fiber felt, a phenolic aerogel matrix is prepared, and the phase change material is removed and the ceramicable resin is filled in the pores on the surface of the fiber felt to form a phenolic aerogel and a ceramicable resin. The gradient structure of the matrix regulates material density and ablation resistance.
It realizes the integrity and stability of the integrated structure of composite materials under high-temperature ablation environment, improves mechanical strength, thermal insulation and ablation resistance, and reduces the amount of ablation regression.
Smart Images

Figure CN118684912B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber-reinforced resin-based composite materials, and in particular to a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure and a preparation method thereof. Background Art
[0002] Fiber-reinforced resin-based lightweight ablative composite materials are porous materials with carbon, quartz and other fiber preforms as the reinforcing phase and phenolic aerogel, phenolic foam and the like as the matrix. They have the characteristics of low density, low thermal conductivity, and high ablation carbon residue. They are the lightweight ablative composite materials with the best thermal protection effect known so far, and have a wide range of application scenarios in the fields of re-entry vehicle heat protection soles, hypersonic flight windward surfaces, and civil building insulation structures.
[0003] Because the matrix of fiber-reinforced resin-based lightweight ablative composite materials is porous resin, the resin matrix is very easy to pyrolyze and vaporize in a high-temperature ablation environment, resulting in material weight loss, structural collapse, and aerodynamic shape retreat. In view of the ablation retreat of composite materials, the existing technology mainly performs gradient design on the material, while ensuring the lightness of the material, reducing the ablation weight loss and linear retreat.
[0004] One method for preparing a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure reported so far is to introduce high and low fiber / resin materials on the surface of the composite material by bonding, stitching, etc. The patent application document with publication number CN117698222A reported a method of preparing a gradient material by stitching a fiber cloth, a metal foil layer, and a fiber-reinforced aerogel with a fiber stitching line, and the patent application document with publication number CN111331875A reported a method of preparing a gradient material by bonding an outer prepreg, a strain isolation layer, and a porous inner layer with silicone rubber. However, the surface layer introduced by bonding, stitching, etc. is very easy to peel off under the scouring of high-temperature airflow, and the integrated structure is destroyed, making it difficult to ensure the integrity and stability of the aerodynamic shape of the composite material during a long-term ablation process. Another method is to use a gradient fiber preform as a reinforcing phase, introduce high-content fibers on the surface of the fiber preform by optimizing the weaving method, and further prepare a porous resin matrix in the fiber preform with a gradient structure, and improve the anti-ablation effect of the material by enriching the fibers on the surface of the composite material to reduce the amount of retreat. Since the fiber preform undergoes physical and chemical phenomena such as oxidation and melting in a high-temperature ablation environment, it cannot resist high-temperature ablation for a long time, and cannot prevent the thermal decomposition and oxidation of the resin matrix. Therefore, this method has a poor anti-ablation recession effect. Summary of the invention
[0005] In response to one or more technical problems existing in the prior art, the present invention provides a gradient-structured fiber-reinforced resin-based lightweight ablative composite material and a preparation method thereof. The preparation method provided by the present invention can accurately control the content ratio of the phenolic aerogel matrix and the ceramic resin matrix in the fiber felt, the density of the composite material and the anti-ablation performance, and can meet different needs. The obtained gradient-structured fiber-reinforced resin-based lightweight ablative composite material has excellent mechanical strength, thermal insulation and anti-ablation performance, and can maintain the integrity and stability of the integrated structure of the composite material during long-term ablation.
[0006] In a first aspect, the present invention provides a method for preparing a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, the preparation method comprising the following steps:
[0007] S1. The outer surface of the fiber felt is immersed in the liquefied phase change material until a preset immersion depth is reached, and then cooled to obtain a placeholder fiber felt;
[0008] S2. Immersing the placeholder fiber felt in a phenolic aerogel precursor solution and performing a first curing to obtain a fiber felt wet gel composite material; the phenolic aerogel precursor solution comprises a phenolic resin, a curing agent and a first solvent;
[0009] S3. removing the phase change material in the fiber felt wet gel composite material to obtain a vacant fiber felt wet gel composite material;
[0010] S4. Immersing the outer surface of the vacant fiber felt wet gel composite material in a ceramic resin solution, performing a second curing, and obtaining a gradient structured fiber-reinforced resin-based lightweight ablative composite material; the ceramic resin solution comprises a phenolic resin, a ceramic filler, and a second solvent.
[0011] Preferably, the fiber felt is a fiber mesh needle felt. Preferably, the fiber of the fiber felt is selected from at least one of quartz fiber, carbon fiber and mullite fiber. More preferably, the density of the fiber felt is 0.10-0.50 g / cm 3 ; and / or
[0012] The phase change material is at least one of paraffin, polyethylene, polypropylene, polyethylene glycol, polyacrylate, polybutyl acrylate, polyurethane and urea.
[0013] Preferably, the preset impregnation depth is less than the thickness of the fiber felt, preferably 1 to 10 mm.
[0014] Preferably, the mass ratio of the phenolic resin, the curing agent and the first solvent in the phenolic aerogel precursor solution is 1:0.1-0.3:5-10.
[0015] Preferably, the curing agent is at least one of hexamethylenetetramine, benzenesulfonphthalein chloride and p-toluenesulfonphthalein chloride; and / or
[0016] The first solvent is a polar solvent, preferably at least one of methanol, ethanol, ethylene glycol and acetone.
[0017] Preferably, the mass ratio of the phenolic resin, the ceramic filler and the second solvent in the ceramizable resin solution is 1:0.5-2:1-10.
[0018] Preferably, the ceramic filler is at least one of zirconium boride, silicon carbide, zirconium oxide, silicon oxide, magnesium oxide, aluminum oxide, boron oxide, boron nitride and sodium silicate; and / or
[0019] The second solvent is a polar solvent, preferably at least one of methanol, ethanol and acetone.
[0020] Preferably, S3 includes: immersing the fiber felt wet gel composite material in a third solvent at a preset temperature, and filtering to obtain a vacant fiber felt wet gel composite material; the preset temperature is not lower than the liquefaction temperature of the phase change material and not higher than the boiling temperature of the third solvent;
[0021] Preferably, the third solvent is at least one of toluene, xylene, chloroform, carbon tetrachloride, ether, carbon disulfide, gasoline and diesel.
[0022] Preferably, the first curing temperature is 100-180°C and the time is 3-5h; and / or
[0023] The second curing temperature is 100-180° C. and the time is 3-5 hours.
[0024] In a second aspect, the present invention provides a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, which is prepared by the preparation method described in the first aspect.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] The present invention firstly uses a phase change material to pre-occupy a position on the outer surface of a fiber felt, and prepares a phenolic aerogel with excellent thermal insulation performance inside the fiber felt, then removes the phase change material pre-occupied on the surface of the fiber felt, and finally fills a ceramic resin in the surface pores of the fiber felt to obtain a fiber-reinforced resin-based lightweight ablative composite material with an integrated gradient structure of a phenolic aerogel and a ceramic resin dual matrix. The present invention uses a phase change material to pre-occupy a position on the surface of the fiber felt to reserve space for filling the ceramic resin in the surface pores of the fiber felt, while ensuring that a phenolic aerogel matrix is prepared in an area outside the phase change material occupation area. By regulating the occupation depth of the phase change material, the thickness of the ceramic resin matrix can be accurately controlled, and then the content ratio of the phenolic aerogel matrix and the ceramic resin matrix in the fiber felt, the density of the composite material, the thermal insulation performance and the anti-ablation performance can be regulated, which can meet different use requirements and broaden the application range of the composite material.
[0027] The gradient-structured fiber-reinforced resin-based lightweight ablative composite material provided by the present invention has an integrated structure of dual matrices, and has excellent mechanical strength, thermal insulation performance and ablation resistance. The ceramicizable resin matrix on the outer surface undergoes a ceramic transformation during the ablation process, forming an inorganic liquid film to block heat and oxygen from corroding the interior of the material, thereby reducing the ablation recession of the material, and can enhance the ablation resistance of the composite material in a high-temperature ablation environment, effectively resist high-temperature ablation, and can maintain the integrity and stability of the integrated structure of the composite material during long-term ablation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a preparation flow chart of a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure provided by the present invention;
[0030] Figure 2 This is a macroscopic morphology of a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure provided in Example 1 of the present invention;
[0031] Figure 3 This is a microscopic morphology of the interface of the dual matrix (phenolic aerogel matrix and ceramizable resin matrix) of the fiber-reinforced resin-based lightweight ablative composite material with a gradient structure provided in Example 1 of the present invention;
[0032] Figure 4This is a graph of the ablation retreat data of the fiber-reinforced resin-based lightweight ablative composite material with a gradient structure provided by Examples 1-3 of the present invention at 1700°C;
[0033] Figure 5 This is the corresponding temperature curve of the back side of the fiber-reinforced resin-based lightweight ablative composite material with a gradient structure provided by Examples 1-3 of the present invention when ablated at 1700°C. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] In a first aspect, the present invention provides a method for preparing a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, the preparation method comprising the following steps:
[0036] S1. The outer surface of the fiber felt is immersed in the liquefied phase change material until a preset immersion depth is reached, and then cooled to obtain a placeholder fiber felt;
[0037] S2. Immersing the placeholder fiber felt in a phenolic aerogel precursor solution and performing a first curing to obtain a fiber felt wet gel composite material; the phenolic aerogel precursor solution comprises a phenolic resin, a curing agent and a first solvent;
[0038] S3. removing the phase change material in the fiber felt wet gel composite material to obtain a vacant fiber felt wet gel composite material;
[0039] S4. Immersing the outer surface of the vacant fiber felt wet gel composite material in a ceramic resin solution, performing a second curing, and obtaining a gradient structured fiber-reinforced resin-based lightweight ablative composite material; the ceramic resin solution comprises a phenolic resin, a ceramic filler, and a second solvent.
[0040] It should be noted that the outer surface corresponds to the side of the fiber-reinforced resin-based lightweight ablative composite material with a gradient structure that is close to the heat source during use.
[0041] The present invention firstly uses a phase change material to pre-occupy a position on the outer surface of a fiber felt, and prepares a phenolic aerogel with excellent thermal insulation performance inside the fiber felt, then removes the phase change material pre-occupied on the surface of the fiber felt, and finally fills a ceramic resin in the surface pores of the fiber felt to obtain a fiber-reinforced resin-based lightweight ablative composite material with an integrated gradient structure of a phenolic aerogel and a ceramic resin dual matrix. The present invention uses a phase change material to pre-occupy a position on the surface of the fiber felt to reserve space for filling the ceramic resin in the surface pores of the fiber felt, while ensuring that a phenolic aerogel matrix is prepared in an area outside the phase change material occupation area. By regulating the occupation depth of the phase change material, the thickness of the ceramic resin matrix can be accurately controlled, and then the content ratio of the phenolic aerogel matrix and the ceramic resin matrix in the fiber felt, the density of the composite material, the thermal insulation performance and the anti-ablation performance can be regulated, which can meet different use requirements and broaden the application range of the composite material.
[0042] The inventors found that if a ceramicizable resin is first introduced onto the surface of a material by spraying or brushing and then impregnated with a phenolic aerogel precursor solution to prepare a phenolic aerogel with excellent thermal insulation properties inside the fiber felt to prepare a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, the ceramicizable resin can only be enriched in a shallow depth area on the outer surface of the material, making it difficult to control the impregnation depth of the ceramicizable resin, and the ceramicizable resin is unevenly distributed in the material, easily leaving residual pores.
[0043] According to some specific embodiments, step S1 includes: heating the phase change material to above the liquefaction temperature to obtain a liquefied phase change material, then immersing the outer surface of the fiber felt in the liquefied phase change material until a preset immersion depth is reached, taking it out, and cooling it to solidify the phase change material on the outer surface of the fiber felt to obtain a placeholder fiber felt with the phase change material occupying the placeholder.
[0044] According to some preferred embodiments, the fiber felt is a fiber mesh needle felt. Preferably, the fiber of the fiber felt is selected from at least one of quartz fiber, carbon fiber and mullite fiber. More preferably, the density of the fiber felt is 0.10-0.50 g / cm 3 (For example, it can be 0.10 g / cm 3 , 0.15g / cm 3 , 0.2g / cm 3 , 0.25g / cm 3 , 0.3g / cm 3 , 0.35g / cm 3 , 0.4g / cm 3 , 0.45g / cm 3 or 0.5g / cm 3 ).
[0045] According to some preferred embodiments, the phase change material is at least one of paraffin, polyethylene, polypropylene, polyethylene glycol, polyacrylate, polybutyl acrylate, polyurethane and urea.
[0046] According to some preferred embodiments, the preset impregnation depth is less than the thickness of the fiber mat, preferably 1 to 10 mm (for example, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm). The present invention controls the depth of impregnation of the phase change material in the fiber mat to control the occupation depth of the phase change material and thus controls the thickness of the ceramic resin matrix, the content ratio of the phenolic aerogel and the ceramic resin matrix in the fiber mat, the density of the composite material and the anti-ablation performance, so as to meet different use requirements and broaden the application range of the composite material.
[0047] According to some preferred embodiments, the mass ratio of the phenolic resin, the curing agent and the first solvent in the phenolic aerogel precursor solution is 1:0.1-0.3:5-10.
[0048] According to some preferred embodiments, the curing agent is at least one of hexamethylenetetramine, benzenesulfonphthalein chloride, and p-toluenesulfonphthalein chloride; and / or
[0049] The first solvent is a polar solvent, preferably at least one of methanol, ethanol, ethylene glycol and acetone.
[0050] According to some preferred embodiments, the mass ratio of the phenolic resin, the ceramic filler and the second solvent in the ceramizable resin solution is 1:0.5-2:1-10.
[0051] According to some preferred embodiments, the ceramizable resin solution further includes a curing agent; the inventors found that adding a curing agent is beneficial to promoting the curing of the resin, and the mass ratio of the phenolic resin, the ceramic filler, the curing agent and the second solvent is 1:0.5-2:0.1-0.3:1-10.
[0052] According to some preferred embodiments, the ceramic filler is at least one of zirconium boride, silicon carbide, zirconium oxide, silicon oxide, magnesium oxide, aluminum oxide, boron oxide, boron nitride and sodium silicate.
[0053] According to some preferred embodiments, the second solvent is a polar solvent, preferably at least one of methanol, ethanol and acetone.
[0054] According to some preferred embodiments, S3 includes: immersing the fiber felt wet gel composite material in a third solvent at a preset temperature, and filtering to obtain a vacant fiber felt wet gel composite material; the preset temperature is not lower than the liquefaction temperature of the phase change material and not higher than the boiling temperature of the third solvent;
[0055] Preferably, the third solvent is at least one of toluene, xylene, chloroform, carbon tetrachloride, ether, carbon disulfide, gasoline and diesel.
[0056] The present invention immerses the fiber felt wet gel composite material in a third solvent under a temperature condition above the liquefaction temperature of the phase change material, thereby ensuring that the phase change material in the composite material is liquefied so that the phase change material can flow out of the composite material during the filtration process accompanied by the flow of the solvent, thereby improving the removal efficiency of the phase change material.
[0057] According to some preferred embodiments, the first curing temperature is 100-180°C (for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C), and the time is 3-5h (for example, 3h, 3.5h, 4h, 4.5h or 5h); and / or
[0058] The second curing has a temperature of 100-180°C (for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C) and a time of 3-5h (for example, 3h, 3.5h, 4h, 4.5h or 5h).
[0059] In a second aspect, the present invention provides a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, which is prepared by the preparation method described in the first aspect.
[0060] The gradient-structured fiber-reinforced resin-based lightweight ablative composite material provided by the present invention has an integrated structure of dual matrices, and has excellent mechanical strength, thermal insulation performance and ablation resistance. The ceramicizable resin matrix on the outer surface undergoes a ceramic transformation during the ablation process, forming an inorganic liquid film to block heat and oxygen from corroding the interior of the material, thereby reducing the ablation recession of the material, and can enhance the ablation resistance of the composite material in a high-temperature ablation environment, effectively resist high-temperature ablation, and can maintain the integrity and stability of the integrated structure of the composite material during long-term ablation.
[0061] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.
[0062] Example 1
[0063] S1. Preparation of placeholder fiber felt: at 70°C, a density of 0.15 g / cm 3 The outer surface of the quartz fiber mesh needle felt is immersed in liquefied paraffin wax, and after the immersion depth reaches 3 mm, the fiber felt is removed to room temperature to obtain a placeholder fiber felt containing a phase change material on the outer surface;
[0064] S2. Preparation of fiber felt wet gel material: The placeholder fiber felt is immersed in a polytetrafluoroethylene mold filled with phenolic aerogel precursor solution (phenolic resin (PR), hexamethylenetetramine (HMTA) and ethanol (EG) are mixed in a mass ratio of 1:0.1:5 and stirred at high speed until the mixture is uniform) under a vacuum degree of -0.1 MPa, and after maintaining the pressure for 2 hours, the mixture is cured at 180°C for 3 hours, and removed after the curing is completed to obtain a fiber felt wet gel material;
[0065] S3. Preparation of vacant fiber felt wet gel material: Immerse the fiber felt wet gel material in xylene solvent at 70°C for 2h, remove it, and filter it from the outer surface to remove paraffin and xylene. Filter it until no liquid drips out of the liquid outlet of the device, and obtain a vacant fiber felt wet gel material;
[0066] S4. Preparation of fiber-reinforced resin-based lightweight ablative composite materials with a gradient structure: Use a ceramicizable resin solution (phenolic resin (PR), zirconium boride filler and ethanol (EG) in a mass ratio of 1:1:10, which are stirred at high speed until they are evenly mixed) to impregnate the outer surface of the vacant fiber felt wet gel material. After sufficient impregnation, remove the material and cure it at 180°C for 3 hours to obtain a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure.
[0067] The macroscopic morphology of the gradient structure fiber-reinforced resin-based lightweight ablative composite material prepared in this embodiment is as follows: Figure 2 As shown, the material specification is 150*150*30mm 3 The outer surface area of the material is a ceramic resin matrix with an impregnation depth of about 2 to 3 cm; the lower area is a phenolic aerogel matrix with an impregnation depth of 22 to 23 cm. The volume density of the composite material is 0.41 g / cm 3 The microscopic morphology of the interface between the phenolic aerogel matrix and the ceramizable resin matrix in the composite material is shown in Figure 2. Figure 3 As shown, there is a nonlinear transition interface between the matrices, and the ceramic resin fills the vacant pores in the fiber felt, forming a transition region where the ceramic resin matrix and the phenolic aerogel matrix coexist. The room temperature thermal conductivity of the gradient structure fiber-reinforced resin-based lightweight ablative composite material prepared in this embodiment is 0.035 W / (mK), and the tensile strength can reach 11 MPa.
[0068] Examples 2-7 and Comparative Example 1 of the present invention are substantially the same as Example 1, with the differences being shown in Table 1.
[0069] Table 1. Comparison of preparation parameters and properties of composite materials in the examples of the present invention and the comparative examples
[0070]
[0071] It should be noted that the linear ablation retreat rate table and weight loss rate in Table 1 are 1700°C flame ablation data. As can be seen from Table 1, the present invention uses phase change materials to pre-occupy positions in fiber felts to prepare an integrated gradient structure fiber-reinforced resin-based lightweight ablative composite material having a phenolic aerogel and a ceramic resin dual matrix, and controls the content ratio of phenolic aerogel and ceramic resin in the fiber felt by adjusting the phase change material occupation depth, and controls the density of the composite material and the anti-ablation performance. The ceramic resin matrix on the outer surface undergoes a ceramic transformation during the ablation process, forming an inorganic liquid film to block heat and oxygen from corroding the inside of the material, thereby reducing the ablation retreat of the material. The weight loss rate of the 1700°C flame ablation material is less than 0.02g / s, and the linear ablation retreat rate is not higher than 0.02mm / s, which is "orders of magnitude" lower than the linear ablation retreat rate (0.17mm / s) of the traditional PICA ablation thermal protection material.
[0072] The ablation retreat data of the fiber-reinforced resin-based lightweight ablative composite material with gradient structure provided in Examples 1-3 of the present invention at 1700°C are as follows: Figure 4 As shown, the ablation heat flux condition is 1.5MW / m 2 -90 s, sample size is φ30*30mm 3 The corresponding temperature curve of the back side of the fiber-reinforced resin-based lightweight ablative composite material with a gradient structure and a thickness of 30 mm provided in Examples 1-3 of the present invention when ablated at 1700° C. is as follows: Figure 5 As shown, the ablation heat flux condition is 1.5MW / m 2 -90 s, material sample size is φ30*30mm 3 The back surface temperatures of Example 1, Example 2, and Example 3 when the firing was stopped at 90s were 60°C, 57°C, and 58°C, respectively.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, characterized in that: The preparation method comprises the following steps: S1. The outer surface of the fiber felt is immersed in the liquefied phase change material until a preset immersion depth is reached, and then cooled to obtain a placeholder fiber felt; S2. Immersing the placeholder fiber felt in a phenolic aerogel precursor solution and performing a first curing to obtain a fiber felt wet gel composite material; the phenolic aerogel precursor solution comprises a phenolic resin, a curing agent and a first solvent; S3. removing the phase change material in the fiber felt wet gel composite material to obtain a vacancy fiber felt wet gel composite material; the phase change material is at least one of paraffin, polyethylene, polypropylene, polyethylene glycol, polyacrylate, polybutyl acrylate, polyurethane and urea; S4. Immersing the outer surface of the vacant fiber felt wet gel composite material in a ceramic resin solution, performing a second curing, and obtaining a gradient structured fiber-reinforced resin-based lightweight ablative composite material; the ceramic resin solution comprises a phenolic resin, a ceramic filler, and a second solvent.
2. The preparation method according to claim 1, characterized in that: The fiber felt is a fiber web needle-punched felt.
3. The preparation method according to claim 2, characterized in that: The fibers of the fiber felt are selected from at least one of quartz fibers, carbon fibers and mullite fibers.
4. The preparation method according to claim 3, characterized in that: The density of the fiber felt is 0.10-0.50 g / cm 3 .
5. The preparation method according to claim 1, characterized in that: The preset impregnation depth is less than the thickness of the fiber felt.
6. The preparation method according to claim 5, characterized in that: The preset immersion depth is 1-10 mm.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the phenolic resin, the curing agent and the first solvent in the phenolic aerogel precursor solution is 1:0.1-0.3:5-10.
8. The preparation method according to claim 1, characterized in that: The curing agent is at least one of hexamethylenetetramine, benzenesulfonphthalein chloride and p-toluenesulfonphthalein chloride; and / or The first solvent is a polar solvent.
9. The preparation method according to claim 8, characterized in that: The first solvent is at least one of methanol, ethanol, ethylene glycol and acetone.
10. The preparation method according to claim 1, characterized in that: The mass ratio of the phenolic resin, the ceramic filler and the second solvent in the ceramizable resin solution is 1:0.5-2:1-10.
11. The preparation method according to claim 1, characterized in that: The ceramic filler is at least one of zirconium boride, silicon carbide, zirconium oxide, silicon oxide, magnesium oxide, aluminum oxide, boron oxide, boron nitride and sodium silicate; and / or The second solvent is a polar solvent.
12. The preparation method according to claim 11, characterized in that: The second solvent is at least one of methanol, ethanol and acetone.
13. The preparation method according to claim 1, characterized in that: S3 includes: at a preset temperature, immersing the fiber felt wet gel composite material in a third solvent, and filtering to obtain a vacant fiber felt wet gel composite material; the preset temperature is not lower than the liquefaction temperature of the phase change material and not higher than the boiling temperature of the third solvent.
14. The preparation method according to claim 13, characterized in that: The third solvent is at least one of toluene, xylene, chloroform, carbon tetrachloride, ether, carbon disulfide, gasoline and diesel.
15. The preparation method according to claim 1, characterized in that: The first curing temperature is 100-180°C and the time is 3-5h; and / or The second curing temperature is 100-180° C. and the time is 3-5 hours.
16. A fiber-reinforced resin-based lightweight ablative composite material with a gradient structure, characterized in that: The method is prepared according to any one of claims 1 to 15.
